Computation of Equilibria in OLGModels with Many Heterogeneous Households - Sebastian Rausch; Thomas F. Rutherford (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
This paper develops a decomposition algorithm by which a market economy with many households may be solved through the computation of equilibria for a sequence of representative agent economies. The paper examines local and global convergence properties of the sequential recalibration (SR) algorithm. SR is then demonstrated to efficiently solve Auerbach- Kotlikoff OLG models with a large number of heterogeneous households. We approximate equilibria in OLG models by solving a sequence of related Ramsey optimal growth problems. This approach can provide improvements in both efficiency and robustness as compared with simultaneous solution methods.
Keywords: C68; C81; D61; D91; 330; Computable general equilibrium; Overlapping generations; Microsimulation; Sequential recalibration; CGE-Modell; Allgemeines Gleichgewicht; Dekompositionsverfahren; Overlapping Generations; Theorie